Nanoparticle aided glycovariant biomarkers for monitoring lung cancer - Sahlman, Saara (My University, 2023)
Lung cancer is no. 1 in cancer related cause of deaths worldwide in both sexes, according to WHO. Lung cancers high mortality rate is mainly caused by late diagnosis. Most patients have stage III or IV disease at the time of diagnosis. Common treatments for lung cancer are surgery, radiofrequency ablation, radiation therapy, chemotherapy, targeted drug therapy, immunotherapy, and palliative procedures. The ability to monitor cancer response to various treatments would help in selecting the most effective therapy forms. Glycoproteins are cells main components. Glycosylation enables high variation of different protein functions. Numerous glycoproteins are used as cancer biomarker with different cancers. However, because they are also found in other benign disease conditions along with healthy individuals and hence lack specificity. Cancer cells differ highly from normal cells, they also have their own altered glycosylation patterns. These altered glycoproteins are specific to the cancer and are highly promising target to search for new biomarkers. Glycan binding proteins include for e.g., lectins and antibodies that bind specifically to certain glycan structures. They are found in all living organisms and hence have highly variable targets. In this study, we use lectins to find different glycoforms of CA19-9, CA15-3, and CA125 glycoproteins from lung cancer patients EDTA plasma samples. Due to the low dissociation constant of lectins, we coat them on highly fluorescent europium chelate dyed nanoparticles to increase the binding affinity. Seven different capture F(ab)2 were used to track different glycoproteins: C192, C241, C242, Ma552, Ma695, Ov185 and Ov197 and six different lectins to detect different glycoforms: MGL, MBL, TJA II, AOL, WGA, and UEA I. We found that three CA19-9 glycovariants (C192-WGA, C241-TJA II and C241- AOL) and one CA15-3 glycovariant (Ma552-TJA II) followed most effectively the progressive and regressive lung cancer disease in patients over time. Standards were established and the glycovariant assays showed good linearity. Results were compared to CA19-9 and CA15- 3 commercial kits from Fujirebio, and it was observed that it is beneficial to detect specific glycovariant instead of the glycoprotein itself. Overall, these four glycovariant based assays show potential for use in monitoring of lung cancer.
Keywords: lung cancer, biomarker, glycovariant, lectin, immunoassay, nanoparticle